Marko Andrijić i njegov doprinos dalmatinskom renesansnom graditeljstvu : doktorski rad = Marko Andrijić and his contribution to Dalmatian Renaissance architecture : doctoral thesis - Nikšić, Goran (Goran Nikšić, 2012)
Sažetak/Summary (prelim. str.)